The survival and control of Salmonella in low water activity foods' environments - Margas, Edyta (2016)
A number of large scale Salmonella outbreaks have been associated with low aw food products where the significant causal factor was most likely cross-contamination. These studies sought to both: assess Salmonella survival and survival mechanisms when dried onto stainless steel under simulated food factory conditions, and to develop enhanced factory control approaches for this pathogen. Fifteen isolates of Salmonella survived 30 days under desiccation and one strain survived for one year and potentially could survive longer. Differences in the survival between different Salmonella serotypes, and isolates of the same serotype (S. Typhimurium), were noted. A 2-population Weibull model was used to model survival, since following an initial reduction in viability (72 h), no further reduction was seen. There was enhanced survival of Salmonella at lower temperatures and relative humidity, with the presence of food debris and when water was added. At a physiological level, attributes associated with osmoresistance (RDAR phenotype, motility, filamentation, EPS production) were not observed in all desiccation resistant strains, additionally survival was greater on surfaces rather than in hyperosmotic solutions. Desiccated cells did not show increased sodium hypochlorite and propanol resistance. To assess molecular survival mechanisms, three RNA extraction methods were compared and real-time RT-PCR was performed for 13 genes. All selected housekeeping genes showed change in expression therefore were not used. Genes in desiccation sensitive strain had higher fold change during desiccation than in resistant strain (aceA, nifU and otsB). The principles of HACCP were reviewed and a prerequisite management programme, based on a risk assessment of sources and vectors, was designed and applied in a low aw food factory, to help control Salmonella cross-contamination. These results suggest the potential for extended survival of Salmonella in food factories, describe the most suitable model to predict survival kinetics, give some insight into Salmonella survival mechanisms and stress responses under desiccation conditions and identify strains and methods for further research studies. The results also confirm the need to keep low aw factories free of food debris and to eliminate water to reduce Salmonella survival. Given the potential for Salmonella survival, the results also highlight the need for the control of cross contamination to the food product via an improved prerequisite management plan.